Analisis Kinerja Sistem Pendingin pada Mesin Toyota Avanza Tipe K3-Ve Menggunakan Scanner Lauch Thinkdiag Easydiag 4.0 - Rizky Sukma Winda; Wisnu Aji Wicaksono; Parikhin (Politeknik Piksi Ganesha Indonesia, 2021)
Every car engine is equipped with a cooling system that functions to maintain the engine temperature while working so that overheating does not occur and of course keeps the engine in good condition. The purpose of this research is to find out how the cooling system on the Toyota Avanza K31-VE engine and the temperature of the coolant when the engine is running. This study uses a descriptive method with data collection from the Thinkdiag Easydiag 4.0 launch scanner. The first step is to start the engine for a total period of 11 minutes and scanned using a scanner, when the engine's stationary position on the scanner shows a coolant temperature of 161.6 Degree F, engine speed of 998 rpm, and throttle sensor position 0. %. Followed by playing the gas pedal until the final results of the research obtained from the scanner are coolant temperature 208.4 Degree F, engine speed 751 rpm, and throttle position sensor 0%.